Platforming Effect in Rendering Culturonyms` Coinage at the Expert Translation and Interpreting Level in International Activities - T. I. Makarevich; I. I. Makarevich; O. I. Makarevich (Концепт: философия, религия, культура, 2023)
The given paper views the impact of the process of platforming and digital translation platforms (DTP) on the rendering of cultural meaning in the dialogue of cultures at the expert translation and interpreting level. The main topic is the problem of finding mechanisms for preventing loss and distortion of the meaning of key cultural concepts in the digital age. The authors aim at analyzing methods of adequate translation and interpreting of the interlinguistic meaning of culturonyms (key cultural concepts) as influenced by platforming processes and DTP use, and their unambiguous understanding by representatives of foreign-language culture, including these interpretations in the dictionary-manual elaborated by the authors. The issue in question is the inclusion into the dictionary-manual the adequate translation determining interlanguage correlation, new culturonyms,unknown cultural meanings, and revealing and describing hidden meanings of English and Russian culture-specific elements and idioms. The authors applied a culturally oriented approach to translation and interpreting that has showed the diversity and cultural value of culturerelated codes. The cultural analysis has indicated most significant culturonyms. The authors have systematized examples of the use of cultural concepts and their translation into Russian in the word entries within the dictionary-manual, which now comprises 151 word entries. A contrastive analysis of nonequivalent lexis has revealed lacunae and non-included meanings in both printed and electronic dictionaries. The heuristic method has been used to create open-type heuristic translation tasks. The authors have received practical approval of the results. The empirical research method was used to analyze digitalization processes and assess the suitable DTP for the research purposes. The dictionary proposed herein is of theoretical and practical significance in new understanding of culturonyms, training foreign affairs specialists, and may be used in teaching translation and interpreting in higher school linguistic and cultural studies, creative education, as well as in business consulting for international companies.